Usability of ICT For Teaching Islamic Studies Concepts in Senior Secondary Schools - Sanusi, Ramat Abidemi; Bolaji, Hammed Olalekan (Universitas Pendidikan Ganesha, 2024)
Proper usability of information and communication tools in teaching Islamic studies concept enhances students’ performance in the subject. However, there has been no research that discusses the level of use of ICT tools among high school Islamic studies teachers. This study aims at working on the level of usability of ICT tools among high school Islamic studies teachers based on availability and accessibility. Descriptive survey research design was used in the study. Two research questions were used for the study. The research instrument used was an adapted questionnaire titled Usability of ICT in Teaching Islamic Studies Concept (UICTTISC). A purposive sampling technique was used to select fifteen Islamic studies teachers as a sample for the study. The data collected from the study were analyzed through descriptive statistics, focusing on frequency counts and basic percentages. The findings of the study revealed that Islamic studies teachers’ accessibility level of ICT tools to teach Islamic Studies was high. The latest information in this research has implications for developing educational policies to maximize ICT empowerment and in the future can improve the quality of learning. As an improvement effort, government should train and re-train teachers on the proper usability of ICT in teaching Islamic studies in Senior Secondary Schools.